Edge plasma dynamics during L-H transition in the JFT-2M tokamak*This article is dedicated to the memory of Professor Tihiro Ohkawa. (1st May 2015) - Kobayashi, T.; Itoh, K.; Ido, T.; Kamiya, K.; Itoh, S.-I.; Miura, Y.; Nagashima, Y.; Fujisawa, A.; Inagaki, S.; Ida, K.; Hoshino, K.
Abstract: This article presents a radial electric field measurement by a heavy ion beam probe in the JFT-2M tokamak, during the L-H transition. An abrupt increase (time scale of O(100 µ s)) of the strong edge radial electric field (localized in the radius with FWHM ∼7 mm) results in the increase of density gradient and turbulence reduction. Rapid inward propagation of the turbulence suppression front is observed at the transition. After the transition, the electric field structure in the tiny edge localized modes (ELMs) is analyzed. Transport self-regulation events observed in the vicinity of the L-H transition, i.e. the limit cycle oscillation (LCO) in the L-mode, the tiny ELM in the H-mode, as well as the L-H transition itself, are summarized in a single Lissajous diagram in the electric field-density gradient space, which provides a comprehensive explanation of the transition dynamics.